MoS2-mesoporous LaFeO3 hybrid photocatalyst: Highly efficient visible-light driven photocatalyst. (14th April 2020) - Acharya, S.; Swain, G.; Parida, K.M.
Abstract: Perovskite type materials have high potential photocatalytic application towards both hydrogen energy generation and organic dye degradation due to their high stability and good reusability. Here, it is the first analysis of photocatalytic degradation of RhB and hydrogen energy evolution under visible light over MoS2 /LaFeO3 nanocomposite. The physicochemical properties of the materials were characterized using a range of techniques such as XRD, TEM, XPS, FTIR, PL, photocurrent, etc. The optical properties of the nanocomposite show good absorption in UV-Vis spectra as compared to the bare LaFeO3 . In this study, MoS2 /LaFeO3 nanocomposite was synthesized through single step in situ hydrothermal processes with a narrow bandgap, enhanced photocatalytic application under visible light. This novel MoS2 /LaFeO3 nanocomposite is an efficient and promising photocatalyst for both hydrogen energy evolution and organic dye degradation. Graphical abstract: MoS2 /LaFeO 3 solid-solid interface showing enhanced hydrogen production and Rhodamine B degradation ability under visible light irradiation. Image 1 Highlights: An approach to fabricate MoS2 /LaFeO3 composite for water reduction and RhB degradation. MoS2 /LaFeO3 composite was synthesized through a single step in situ hydrothermal process. A composite synthesized with a narrow band gap, enhanced photocatalytic application. Activity is due to interfacial interaction among MoS2 and LaFeO3 through self-assembly approach.